1998
DOI: 10.1111/j.1365-2109.1998.tb01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light intensity, tank colour and photoperiod on swimbladder inflation success in larval striped bass, Morone saxatilis (Walbaum)

Abstract: Striped bass, Morone saxatilis (Walbaum)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 18 publications
0
35
0
1
Order By: Relevance
“…It is believed that many physoclistic teleosts, such as seahorses, have to ingest air to initially inflate the swimbladder (Steen 1970;Martin-Robichaud & Peterson 1998). If juvenile H. abdominalis are confused by the white tank coloration, and if the pneumatic duct connecting the foregut and swimbladder closes before successful inflation, ingestion of air by the juveniles in an attempt to fill their swimbladders could result in air bubbles trapped within the gut.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that many physoclistic teleosts, such as seahorses, have to ingest air to initially inflate the swimbladder (Steen 1970;Martin-Robichaud & Peterson 1998). If juvenile H. abdominalis are confused by the white tank coloration, and if the pneumatic duct connecting the foregut and swimbladder closes before successful inflation, ingestion of air by the juveniles in an attempt to fill their swimbladders could result in air bubbles trapped within the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have concentrated on showing the effects of environmental colors on some mammals (1), birds (2) and fish (3), but the mechanisms are still unknown. In fish, some studies have shown that environmental color affects growth (4)(5)(6), feeding (7)(8)(9), food conversion rate (10), stress (10,11), aggression (12), and egg development (13).…”
mentioning
confidence: 99%
“…Intermediary photoperiods were also better for larvae survival of other species at the beginning of the feeding (Barahona-Fernandes, 1979;Martin-Robichaud and Peterson, 1998).…”
Section: Discussionmentioning
confidence: 99%